A clinical report demonstrating the significance of distinguishing a nasopalatine duct cyst from a radicular cyst. (18th March 2014) - Aparna, Manikkath; Chakravarthy, Arumugam; Acharya, Shashi Rashmi; Radhakrishnan, Raghu
Abstract : Endodontic diagnosis is challenging and depends on the organisation of information from the patient history, clinical examination and analysis of the pulp, radiographic and histopathological assessment. A 35-year-old man was endodontically treated for radiolucency in relation to the roots of maxillary central incisors as it was a provisionally diagnosed case of radicular cyst. Since the palatal swelling persisted, the lesion was re-evaluated using relevant diagnostic aids and a diagnosis of nasopalatine duct cyst (NPDC) was made, which was missed during the initial assessment. An erroneous interpretation of cystic radiolucency in relation to maxillary central incisors can often lead to inappropriate treatment planning. This case highlights the relevant aspects in the diagnosis of NPDC when it is mistaken for a radicular cyst and emphasises the need for thorough clinical examination and relevant investigations for periapical radiolucencies of questionable origin before initiating endodontic therapy.